الاستقلالية المالية للجماعات المحلية - شهيــــرة، سبــوعــي; زهيـــــرة ،مناعـــــي (جامعة الوادي University of El Oued, 2024)
إن الدراسة تهدف إلى توضيح أن مبدأ اللامركزية يفرض استقلالية الجماعات المحلية والإقليمية إداريا وماليا، حيث تكون من جهة مستقلة في أداء مهامها، ومن جهة أخرى تتمتع باستقلالية مالية للاضطلاع بهذه المهام، ويلازم كل توسيع في الصلاحيات، زيادة في الموارد المالية المخصصة لها وبذلك يمكن القول أن الموارد المالية هي عنصر أساسي للاستقلال المحلي بحيث إذا لم تكن لها موارد مالية مستقلة، فإن الاستقلال يعتبر ناقصا ويحول دون ممارستها لاختصاصاتها، ذلك أن تدعيم اللامركزية الإدارية ورفع قدرتها على القيام باختصاصاتها إنما يعتمد على الموارد المالية المتاحة لها. تعد البلدية والولاية التنظيم الإداري المحلي المتبني في الجزائر منذ الاستقلال، واللذان مرّا بعدة إصلاحات، هذه الأخيرة التي سوف لن تؤدى على أكمل وجه ما لم تكن مصحوبة باستقلالية مالية تبنى امتلاك موارد مالية ذاتية مصحوبة بحرية في التسيير. نظرا لأهمية التي يحتلها الجانب المالي رفي تجسيد اللامركزية، فقد أرنا تخصيص موضوع الدراسة لبيان مدى استطاع هذا البعد إن يؤثر في رسم أو تحديد المعالم الحقيقة لمفهوم الاستقلالية المحلية. This study aims at highlighting that the principal of decentralization requires the local and regional communities' administrative and financial independence. For, on the one hand these communities or groups are independent in performing their justifications, and on the other hand, they need to enjoy financial independence to perform them. Therefore, every expansion of their powers is accompanied by an increase in the financial resources allocated to them. Accordingly, it is appropriate to say that financial resources are an essential element of local independence. As, if a group does not have independent financial resources its independence is considered incomplete, because it prevents it from exercising its jurisdictions. Consequently, reinforcing administrative decentralization and increasing its ability to perform its jurisdictions depends on the financial resources available to it. The municipality and the state are the local administrative organization adopted in Algeria since its independence, both of which have undergone several reforms. These reforms will not be fully effective unless accompanied by financial independence that involves owning self-funded financial resources with managerial freedom. Due to the importance of the financial aspect in embodying decentralization, we have chosen to allocate the study topic to demonstrate the extent to which this dimension can influence the delineation of the true features of the concept of local independence.
ماستر اداري